1987
DOI: 10.3109/02713688709025202
|View full text |Cite
|
Sign up to set email alerts
|

Changes in the oscillatory potentials of the electroretinogram in glaucoma

Abstract: Dark adapted and progressively light adapted electroretinograms (ERGs) were recorded from 34 normals and from 45 glaucoma patients. To enhance the oscillatory potentials (OP) the ERGs were highpass-filtered. The OP were characterized by two indices: their root-mean-square value and the inter-flash interval for which the maximal amplitude was obtained. In most of the glaucomatous OP, 50 of 81 eyes, both indices were abnormal, in 22 one parameter was abnormal and only in 9 were both parameters normal. In 13 of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
29
0

Year Published

1989
1989
2013
2013

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(31 citation statements)
references
References 12 publications
2
29
0
Order By: Relevance
“…A reduction of OPs in patients with glaucoma or optic nerve diseases has been reported (Gur 1987;Vaegan 1995) but this does not necessarily correlate with the extent of damage in individual patients. It has been suggested (Vaegan 1991;Vaegan 1994;Vaegan 1995) that changes in the ganglion cell dendrites might cause the reduction in OPs.…”
Section: Discussionmentioning
confidence: 99%
“…A reduction of OPs in patients with glaucoma or optic nerve diseases has been reported (Gur 1987;Vaegan 1995) but this does not necessarily correlate with the extent of damage in individual patients. It has been suggested (Vaegan 1991;Vaegan 1994;Vaegan 1995) that changes in the ganglion cell dendrites might cause the reduction in OPs.…”
Section: Discussionmentioning
confidence: 99%
“…Some reports have challenged the belief that the¯ash ERG is essentially normal after optic nerve damage or in glaucoma, as discussed by Korth (1997). These reports demonstrated that glaucoma can affect components of thē ash ERG, such as scotopic ERG amplitude and implicit time changes (Alvis, 1966;Ogata, 1976;Wanger and Persson, 1983;Fazio et al, 1986;Lambrou and Greve, 1989), an altered scotopic threshold response (Korth, Nguyen and Martus, 1994;Frishman et al, 1996), changes in oscillatory potentials (Gur et al, 1987;Vaegan et al, 1995), reduced responses to¯icker (Alvis, 1966;Holopigian et al, 1990;Odom et al, 1990), and reduced cone-mediated ERG b-wave amplitude and prolonged implicit times (Holopigian et al, 1990;Vaegan et al, 1991).…”
Section: Discussionmentioning
confidence: 99%
“…Consistent with this, a decrease in the amplitude of oscillatory potentials, presumed to be generated by amacrine cells, has been reported in human glaucomatous eyes. 62 Future studies should address the functional status of amacrine cells following microvasculature loss in glaucoma.…”
Section: Discussionmentioning
confidence: 99%